Respon Broiler Terhadap Pemanfaatan Bungkil Inti Sawit Fermentasi Dalam Ransum (Utilization fermented of palm kernel cake in broiler diet) - Mirnawati Mirnawati (Jurnal Embrio, 2012)
An experiment was conducted to know utilization fermented of palm kernel cake (FPKC) by A. niger as a substitute for soybean meal in the broiler ration. The experiment used a complete randomize design (CRD) with 5 treatments and 4 replications. The treatments were arranged as follows: 1) 0% basic ration (0% FPKC), 2) 25% substitution of soybean meal with FPKC, 3) 50% substitution of soybean meal with FPKC, 4) 75% substitution of soybean meal with FPKC, 5) 100% substitution of soybean meal with FPKC. The ration were formulated in iso protein 22% and iso caloric 3000 kkal /kg ration. The parameters of this study were feed intake, body weight gained, feed conversion and percentage of carcas. The results of this study showed that feed intake, body weight gained, feed conversion and percentage of carcas were not significantly affected (P>0,05) by any treatment. The conclusion fermented of palm kernel cake (FPKC) by A. niger as a substitute for soybean meal in the broiler ration can be 100% a substitute of soybean meal or 18% in broiler ration.